Erratum: Thermophysical Studies of Dibenzyltoluene and Its Partially and Fully Hydrogenated Derivatives (Journal of Chemical and Engineering Data (2018) 63:12 (4580−4587) DOI: 10.1021/acs.jced.8b00652) - Aslam, Rabya; Khan, Muhammad Hashim; Ishaq, Muhammad; Müller, Karsten (Journal of Chemical and Engineering Data, 2021)
In a previous version of the article, the affiliations of Muhammad Hashim Khan, Muhammad Ishaq, and Karsten Mu¨ller were exchanged. At the time of the article submission, Muhammad Hashim Khan and Muhammad Ishaq were at the Institute of Chemical Engineering & Technology of the University of the Punjab, while Karsten Mu¨ller was at the Institute of Separation Science and Technology of the Friedrich-Alexander-Universita¨t Erlangen-Nu¨rnberg.
CRIS-Team Scopus Importer:2021-02-12